Achene dimorphism and protracted release: a trait syndrome allowing continuous reshaping of the seed-dispersal kernel in the Mediterranean species Pallenis spinosa. (4th July 2018) - Bastida, Fernando; Macías, Francisco J.; Butler, Isabel; González-Andújar, José L.
ABSTRACT: Background : Pallenis spinosa (Asteraceae) produces both winged and wingless achenes. Both achene morphs are non-dormant and show a similar embryo size, rendering dispersal ability as their only apparent functional difference. Aims : We studied morph-specific release and spatial dispersal patterns to ascertain whether the common view of seed dimorphism as a mixed strategy, that is functionally fully differentiated morphs, is appropriate for this system. Methods : For three years, at the onset of achene release, in early autumn, we placed achene traps at different distances from source plants, censusing achene arrival at 3–4 day intervals. We constructed morph-specific dispersal kernels and related release intensity to prevailing meteorological conditions in census intervals. Selected kernel models were used to describe dispersal effects of observed changes in the proportion of winged achenes ( pw ) in successive released fractions. Results : Achene release extended up to early-mid winter, peaking in rainy, windy intervals. Throughout the season, pw decreased progressively. Unexpectedly, the wingless morph produced the longest dispersal tails and it only showed ability for fat-tailed dispersal. Consequently, maximum dispersal distances steadily increased throughout the season. Conclusions : Achene dimorphism in P. spinosa appears to allow a within-season continuous reshaping of the seed-dispersal kernel instead of representing a mixed strategy.